Phacoemulsification and calculation of intraocular lenses in patients given keratorefractive surgery. Part 1 - I. E. Ioshin (Российский офтальмологический журнал)
Rationale.Qualitative rehabilitation of patients with cataracts who had keratorefractive surgeries depends on phacoemulsification technology and correctly calculated optical power of the IOL. Purpose: present the author’s own approaches to the development of surgical tactics for treating patients with cataracts who underwent keratorefractive surgeries. Material and methods. The complicated character of cataract surgery performed after LASIK — deterioration of visualization due to the presence of an optical ablation zone and a transition zone (6–7 mm) — is successfully compensated by instillations of a dispersed viscoelastic (methylcellulose) onto the surface of the cornea. Another factor is the deepening of the anterior chamber in high myopia, which is uncomfortable for manipulation and may require a lowerlevel of irrigation (up to 60 mm Hg). The technology of surgery performed after radial keratotomy (RK) requires utmost attention to the prevention of surgical astigmatism that could emerge due to biomechanical instability of the cornea. To ensure such prevention, paracentesis is performed outside the zone of keratotomy scars, the main 2.2 mm incision is made after capsulorhexis in the sclerolimbal zone, and at theend of the operation, a subconjunctival injection is performed in the conjunctival zone of the knife keratom entrance for the tamponade ofthe outer part of the incision without suturing. These techniques made it possible to successfully perform more than 200 operations and achieve a favorable course of the postoperative period from the first day. Fast adaptation of the incision (1–2 days), uncomplicated course of the postoperative period and the absence of induced astigmatism are important advantages of this technology. Conclusion. The choice of surgical technology, taking into account the initial state of the eye after LASIK and RK surgeries, is an important task. Yet the main problem with which the doctor is faced after keratorefractive surgery is the difficulty of calculating the optical power of the IOL which must take into account the special needs of the patient with a particular refractive history, which will be reported in part 2 of the article.